HUBUNGAN ANTARA EDUKASI ILMU BALAGHOH DENGAN KETERTARIKAN MEMPELAJARI TAFSIR AL-QUR’AN PADA PESERTA PROGRAM I’DAD LUGHOWI LANJUTAN - Arif Husnul Khuluq; Inanda Tsabithah Salsabila; Ahyat Habibi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
Balaghoh is a study that discusses words in Arabic, regarding their composition, meaning, as well as the beauty and accuracy in choosing the right words. The Qur’an which is considered to be at the peak of the beauty of language is a holy book that was revealed by Allah to the Prophet Muhammad through the intermediary of the angel Gabriel to mankind, as a guidance of life in this world and the hereafter. The Qur’an Interpretation is a study that helps to uncover and clarify the meaning of the Qur’an verses and extract the laws from it. This study aims to examine the correlation between balaghoh education and interest in studying the Qur’an interpretation. The approach used in this research is quantitative. The population of this study is female students who take part in the Advanced Language Preparation Program. The number of samples is at least 30 students taken by simple random sampling technique. The instrument used is a questionnaire with a Likert scale. The data analysis technique used simple linear regression with the help of SPSS version 23. The results of this study indicated that there is a significant positive correlation between balaghoh education and interest in studying the Qur’an interpretation of the Advanced Language Preparation Program participants. So, the higher the education of balaghoh is, the higher the interest in studying the Qur'an interpretation is. The level of correlation between balaghoh education and interest in studying the Qur'an interpretation is moderate.